2020
DOI: 10.1159/000505123
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Symptom Presentation of Hypercontractile Peristalsis in the Era of High-Resolution Manometry: A Single-Center Experience

Abstract: Background: Hypercontractile motility of the esophagus is occasionally noted on high-resolution manometry (HRM), but its clinical correlations are unclear. We compared symptom severity and clinical presentation of patients with hypercontractile motility of the esophagus. Methods: This was a retrospective cohort study. We queried a prospectively maintained database for patients who underwent esophageal function testing from October 1, 2016, to October 30, 2018. We included patients with jackhammer esophagus (JE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 3 publications
3
11
0
Order By: Relevance
“…The lack of relationships between manometric data and symptoms, especially chest pain, has also been reported previously. 3,4,9,11 of medical treatment has also been reported by others. 9 The endoscopic treatments seemed to provide better success rates than the medical treatments.…”
Section: Ta B L E 1 High-resolution Manometry Parameters In All 232 Psupporting
confidence: 69%
See 2 more Smart Citations
“…The lack of relationships between manometric data and symptoms, especially chest pain, has also been reported previously. 3,4,9,11 of medical treatment has also been reported by others. 9 The endoscopic treatments seemed to provide better success rates than the medical treatments.…”
Section: Ta B L E 1 High-resolution Manometry Parameters In All 232 Psupporting
confidence: 69%
“…In some patients, symptoms, mainly chest pain, may occur during HRM; unfortunately, this was not reported in the clinical reports and could not be analyzed in our cohort. The lack of relationships between manometric data and symptoms, especially chest pain, has also been reported previously 3,4,9,11 . In our present study, only single water swallows have been used during HRM.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…A study in 39 EGJOO patients comparing 15 patients with combined EGJOO and esophageal hypercontractile peristalsis and 24 patients with only EGJOO found no significant difference in demographic data and symptom severity between both groups. 29 Two-thirds of patients in each group reported at least one moderate to severe symptom that affected their daily life. Another study included 56 patients with EGJOO, 44 patients with hypercontractile esophagus, and 33 healthy volunteers.…”
Section: What Is the Clinical Presentation Of Patients With Egjoo?mentioning
confidence: 99%
“…Most of the patients were overweight, with a mean body mass index of 26.5-28.6 kg/m 2 . 16,27,28 Clinical and HRM features of patients with EGJOO Most of the studies reported dysphagia as the most common symptom in EGJOO patients (36-89%), 2,23,24,29,30 followed by retrosternal pain (10-71%) and heartburn and/or regurgitation (8.4-35%). 2,15,[23][24][25][26]30 In a subgroup analysis that included only functional EGJOO, the prevalence of dysphagia decreased to 25-50%.…”
Section: What Is the Clinical Presentation Of Patients With Egjoo?mentioning
confidence: 99%